PELAKSANAAN HAK WARIS ADAT ANAK PEREMPUAN PADA MASYARAKAT MARGA (LAMA) RAMBANG KAPAK TENGAH KOTA PRABUMULIH DI DALAM HUKUM KEWARISAN ISLAM - Astuti Maryulaini (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2015)
Abstract : This thesis entitled “THE IMPLEMENTATION OF THE INDIGENOUS  INHERITANCE RIGHTS OF DAUHGTERS IN THE (OLD) ETHNIC OF THE  RAMBANG KAPAK TENGAH IN PRABUMULIH  BASED ON THE ISLAMIC INHERITNANCE LAW”  was aimed at examining the inheritance rights of daughters seen from Islamic inheritance law and explaining  the legal requirements of the Islamic inheritance law functioning as its legal cover; cause of parental injustice by gift all of the treasures to the sons and none to the daughters; see the role of notaries in issuing the certificate of bequests.  The theory used is the theory of justice, legal protection theory, theory  of Receptio in Complexu, Theory of Receptie a Contrario. This is an empirical study that uses a statutory approach, historical approach, philosophical approach. The data in this research consists of primary legal materials, legal materials and secondary and tertiary legal materials sourced from the legislations. The data were collected by  identifying and inventorying existing legal materials relevant to the legal issues.  The data were structured, described, and systematized  based on the analysis of legal materials by means of analysis and interpretation of the law. Deductive and inductive logic is used to draw conclusions.  It  can be concluded that the customary law of inheritance daughters of the (old) ethnic of the Central  Rambang Kapak in Prabumulih is not in accordance with the system of Islamic inheritance law, especially regarding the division of property inheritance for  sons and daughters which are not based on the division of 2:1 (two equals to one) as stipulated in the QS. An-Nisaa verse 11 and chapter 176 compilation of Islamic law. The Compilation of Islamic law in the case of inheritance can be a source of  law for the (old)  ethnic of Rambang Kapak Tengah in Prabumulih in order to protect the inheritance rights of daughters. Notaries’ role on the issuing  of  bequest certificates in the (old) ethnic of Rambang Kapak Tengah in Prabumulih  is in conformity with the provisions of  the notaries’ law  number 30 of 2004, but the implementation of the Article 15 (2)e that contains a notary obligation to provide legal counseling to their clients has given  less effective impact for (old) ethnic of  the Rambang Kapak Tengah in Prabumulih.Keywords, Daughters,Islamic Inheritance Law